The RNA export and RNA decay complexes THO and TRAMP prevent transcription-replication conflicts, DNA breaks, and CAG repeat contractions. - Rebecca E Brown; Xiaofeng A Su; Stacey Fair; Katherine Wu; Lauren Verra; Robyn Jong; Kristin Andrykovich; Catherine H Freudenreich (PLoS Biology, 2022)
Expansion of structure-forming CAG/CTG repetitive sequences is the cause of several neurodegenerative disorders and deletion of repeats is a potential therapeutic strategy. Transcription-associated mechanisms are known to cause CAG repeat instability. In this study, we discovered that Thp2, an RNA export factor and member of the THO (suppressors of transcriptional defects of hpr1Δ by overexpression) complex, and Trf4, a key component of the TRAMP (Trf4/5-Air1/2-Mtr4 polyadenylation) complex involved in nuclear RNA polyadenylation and degradation, are necessary to prevent CAG fragility and repeat contractions in a Saccharomyces cerevisiae model system. Depletion of both Thp2 and Trf4 proteins causes a highly synergistic increase in CAG repeat fragility, indicating a complementary role of the THO and TRAMP complexes in preventing genome instability. Loss of either Thp2 or Trf4 causes an increase in RNA polymerase stalling at the CAG repeats and other genomic loci, as well as genome-wide transcription-replication conflicts (TRCs), implicating TRCs as a cause of CAG fragility and instability in their absence. Analysis of the effect of RNase H1 overexpression on CAG fragility, RNAPII stalling, and TRCs suggests that RNAPII stalling with associated R-loops are the main cause of CAG fragility in the thp2Δ mutants. In contrast, CAG fragility and TRCs in the trf4Δ mutant can be compensated for by RPA overexpression, suggesting that excess unprocessed RNA in TRAMP4 mutants leads to reduced RPA availability and high levels of TRCs. Our results show the importance of RNA surveillance pathways in preventing RNAPII stalling, TRCs, and DNA breaks, and show that RNA export and RNA decay factors work collaboratively to maintain genome stability.